Looking back : Shakespeare's indebtedness to Chaucer and the representations of Chivalry in King Richard II, The Two Noble Kinsmen, and The Knight's Tale - Han, Cheryl Suling (2013)
This paper considers the continuity—rather than a rupture—between the Middle Ages and the early modern period by exploring Shakespeare’s indebtedness to Chaucer through the appropriation of The Knight’s Tale in The Two Noble Kinsmen. This paper begins with an examination of chivalry in Richard II, demonstrating Shakespeare’s interest in not only the subject matter, which he believed had resonance with the political climate of his day, but also his interest in Chaucer’s England. This constituted a form of retrospective enquiry into the past, and it is from here where we can begin to perceive a closer connection between the two writers. The second chapter deals with intertextuality in Shakespeare and Chaucer’s works, demonstrating the tradition of borrowing, thus situating Shakespeare as an inheritor of a rich legacy of textual references. It also deals with Shakespeare’s appropriation of the Knight’s Tale from which he derived material from The Two Noble Kinsmen, both of which, I argue, were composed to subvert the usually idealised code of conduct by which knights lived that chroniclers tended to depict.